A composite pulp-raising and water-retaining agent synthesized based on six carbon monomers and a preparation method thereof

By building a hydrophilic network on the surface of fine sand and combining it with other components, a composite slurry water retention agent was prepared, which solved the problem of unsatisfactory moisture dispersion in concrete and significantly improved the flowability and processability of concrete.

CN118125745BActive Publication Date: 2025-02-07XINYANG LINGSHI TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410249139.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-05
Publication Date
2025-02-07
Estimated Expiration
2044-03-05

AI Technical Summary

Technical Problem

Existing water retention agents cannot effectively solve the problem of unsatisfactory moisture dispersion in concrete, resulting in a decrease in the processability and fluidity of concrete.

Method used

By cross-linking and polymerizing monomers on the surface of fine sand, a hydrophilic network is constructed and combined with components such as sulfonated candle glue and sulfonated tannins, a composite slurry water retention agent is prepared. This water retention agent not only has the function of water retention, but also improves the dispersion of moisture and the overall processability of concrete.

Benefits of technology

This water-retaining agent can effectively improve the dispersion stability of moisture in concrete, reduce the deposition and water excretion phenomenon, improve the flowability and processability of concrete, and overcome the problems of adsorption loss and uneven water dispersion of traditional water-retaining agents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004727016660000061
    Figure BDA0004727016660000061
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete admixtures, and particularly relates to a composite slurry-raising and water-retaining agent synthesized based on a six-carbon monomer and a preparation method thereof. The composite slurry-raising and water-retaining agent is prepared by fully mixing one or more of the six-carbon monomer, acrylamide and diacetone acrylamide with polyacrylamide and a crosslinking agent to form component A; one or more of acrylic acid, hydroxyethyl acrylate and hydroxypropyl acrylate with methyl acrylate and / or methacrylate and a reducing agent to form component B; in a stirring state, graft-modified fine sand, a catalyst, a chain transfer agent and an oxidant are added to component A, and then component B and an alkali solution are dripped therein, and after the dripping is completed and the reaction is continued for a period of time, one or more of sulfonated tannin, sulfonated tannin, glycerol and lauryl alcohol are added therein, and then water is added to dilute and disperse the mixture to form a water-retaining agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete admixtures, and particularly relates to a composite grouting and water-retaining agent synthesized based on a hexacarbon monomer and a preparation method thereof. Background Art

[0002] With the large-scale construction of highways, railways, hydropower stations, civil engineering and other projects, the performance requirements of high-performance concrete are getting higher and higher. High-performance concrete not only requires fresh concrete to have excellent fluidity, but also requires its fluidity to be maintained for a long time. However, in the actual application process, the loss of water in fresh concrete will reduce the fluidity of concrete and lead to poor workability.

[0003] The addition of water retaining agent can effectively retain water in concrete, reduce water loss, improve the workability of fresh concrete, reduce the amount of water added to concrete during use, change the properties of concrete, and improve strength. Therefore, water retaining agent has become one of the indispensable components for the configuration of high-performance, high-fluidity and high-fluidity retention concrete.

[0004] However, there is another problem in the actual construction process: due to the low solubility between water and concrete matrix, the dispersion of water in the fresh concrete system is not ideal. In the initial stage of water addition construction, water can still be dispersed to various locations inside the concrete, but as the sedimentation effect in the concrete system gradually develops, the uniformity of water distribution in the concrete decreases, which affects the overall processability of the fresh concrete. The current water retaining agent cannot effectively solve this technical problem. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a preparation method of a composite slurry water-retaining agent based on the synthesis of hexacarbon monomers, including the steps of taking materials, surface modification of fine sand, proportioning monomer solution, preparing dripping solution, dripping insulation, adjusting pH, adding functional compounds, etc., and further, a hydrophilic network formed by using hexacarbon monomers, acrylamide, polyacrylamide, diacetone acrylamide, etc. as main polymerization raw materials is coated on the surface of part of the fine sand, with novel structure and reasonable design, and after the reaction is complete, sulfonated tannin, sulfonated tannin, propylene glycol, and lauryl alcohol are compounded and added to obtain the target product anti-adsorption slurry water-retaining agent, which has the functions of filling, anti-adsorption, slurry, water retention and collapse protection for concrete, and has wide adaptability and is suitable for various coarse and fine aggregates treated with flocculants. It overcomes the problems of adsorption loss of water-retaining agent, rapid loss of concrete slump, uneven water dispersion, large fluctuations, etc. in the use of admixtures in the production of ready-mixed concrete.

[0006] The specific method is:

[0007] (1) Grafting modification of fine sand surface by silane coupling agent containing carbon-carbon double bonds

[0008] Ultrasonic dispersion of fine sand in an alcohol solvent, and addition of a silane coupling agent containing a carbon-carbon double bond, an alkali agent, and water thereto, stirring for reaction and then filtering, fully washing the grafted and modified fine sand, filtering, and drying;

[0009] (2) fully mixing one or more of a hexacarbon monomer, acrylamide, and diacetone acrylamide with polyacrylamide and a crosslinking agent to form component A;

[0010] (3) mixing one or more of acrylic acid, hydroxyethyl acrylate, and hydroxypropyl acrylate, methyl acrylate and / or methacrylate, and a reducing agent to obtain component B;

[0011] (4) adding the grafted fine sand, catalyst, chain transfer agent and oxidant obtained in step (1) to component A obtained in step (2) under stirring, and then dripping component B and alkali solution obtained in step (3) thereto, and continuing the reaction for a period of time after the dripping is completed;

[0012] (5) adding one or more of sulfonated tannin, sulfonated tannin, glycerol and lauryl alcohol to the reaction system obtained in step (4), and then adding water to dilute and disperse the mixture sufficiently to serve as a water retaining agent.

[0013] Preferably, in step (1), the particle size of the fine sand is 400 μm to 800 μm.

[0014] Preferably, in step (1), the alcohol solvent is one or more of methanol, ethanol, n-propanol and isopropanol.

[0015] Preferably, in step (1), the alkaline agent is one or more of sodium hydroxide, potassium hydroxide and ammonia water.

[0016] Preferably, in step (1), the mass ratio of fine sand, silane coupling agent containing carbon-carbon double bonds, alkali agent, water and alcohol solvent is 15-20: 5-100: 1-50: 10-200: 300-1500.

[0017] Preferably, in step (1), the reaction temperature of the stirring reaction is 20 to 50° C., and the reaction time is 24 to 96 hours.

[0018] Preferably, in step (1), the drying temperature is 60-80°C.

[0019] Preferably, in step (2), the cross-linking agent is one or more of 1,3-butadienoic acid methyl ester, 2,3-butadienoic acid ethyl ester, and isoprene.

[0020] Preferably, the six-carbon monomer in step (2) is ethylene glycol vinyl ether polyoxyethylene ether.

[0021] Preferably, in step (2), 200 to 340 parts by weight of one or more of the six carbon monomers, acrylamide, and diacetone acrylamide, 5 to 50 parts by weight of polyacrylamide, and 15 to 40 parts by weight of a cross-linking agent are mixed and dispersed in 400 to 600 parts by weight of water.

[0022] Preferably, the reducing agent in step (3) is one or more of L-ascorbic acid, sodium sulfite, sodium bisulfite, glucose monohydrate, and D-isoascorbic acid.

[0023] Preferably, in step (3), 50 to 120 parts by weight of one or more of acrylic acid, hydroxyethyl acrylate, and hydroxypropyl acrylate, 1 to 8 parts by weight of methyl acrylate and / or methacrylate, and 1.5 to 2.5 parts by weight of a reducing agent are mixed and dispersed in 60 to 80 parts by weight of water.

[0024] Preferably, the catalyst in step (4) is one or more of ferrous sulfate, sodium hypophosphite, antimony glycol, and antimony acetate.

[0025] Preferably, the chain transfer agent in step (4) is one or more of mercaptopropionic acid, thioglycolic acid and mercaptoethanol.

[0026] Preferably, the oxidant in step (4) is one or more of ammonium persulfate, potassium persulfate, hydrogen peroxide, tert-butyl hydroperoxide, and dibenzoyl peroxide.

[0027] Preferably, in step (4), component B is added dropwise for 1.5 h, and the alkali solution is added dropwise for 1 to 2 h. After the addition is complete, the reaction is continued for 1 to 2 h.

[0028] Preferably, the stirring temperature in step (4) is 20 to 70°C.

[0029] The present application also provides a composite pulping and water-retaining agent synthesized based on six carbon monomers prepared by the above preparation method.

[0030] The beneficial effect of the present invention is that: the present invention constructs a hydrophilic network on the surface of fine sand through monomer cross-linking polymerization: first, a silane coupling agent containing a carbon-carbon double bond is modified and grafted on the surface of the fine sand, and then a monomer containing a hydrophilic group (such as ethylene glycol vinyl ether polyoxyethylene ether, acrylamide, acrylic acid, hydroxyl acrylate, etc., wherein the carboxyl group, hydroxyl group, amide group, etc. above are all hydrophilic groups) is subjected to addition polymerization reaction with the carbon-carbon double bond on the aforementioned silane coupling agent, thereby chemically connecting these hydrophilic monomers to the surface of the fine sand, wherein the cross-linking agent has two carbon-carbon double bonds in its molecular structure, so that after it participates in the polymerization, a more stable network structure is formed between the polymer chains.

[0031] When the organic-inorganic composite modified fine sand is used as the main component of the water retaining agent and mixed with fresh concrete, the fine sand itself is a conventional component of concrete, and the fine sand, as a particle, forms a solid particle mixture with the effective components of concrete, so that the fine sand can be evenly and stably dispersed in the fresh concrete, and the hydrophilic network grown on the surface of the fine sand through chemical grafting attracts the water in the fresh concrete to play a role in water retention. Therefore, the water is evenly and stably distributed in the fresh concrete through the fine sand with the hydrophilic network on the surface, thereby improving the dispersion stability of the water in the concrete system, which is beneficial to the overall use and processing of the fresh concrete. DETAILED DESCRIPTION

[0032] Example 1

[0033] (1) 20 parts by weight of fine sand (particle size of 700 μm to 800 μm) was ultrasonically dispersed in 1000 parts by weight of ethanol, and 100 parts by weight of vinyl triethoxysilane, 80 parts by weight of ammonia water (NH3 mass concentration of 25%) and 120 parts by weight of water were added thereto, and the mixture was mechanically stirred at room temperature (25° C., the same below) for 48 hours, and then filtered. The obtained filter cake was fully washed in excess ethanol, centrifuged and dried in vacuum at 60° C. to obtain graft-modified fine sand;

[0034] (2) 1400 kg of ethylene glycol vinyl ether polyoxyethylene ether, 1200 kg of acrylamide, 200 kg of polyacrylamide, 50 kg of diacetone acrylamide, and 200 kg of crosslinking agent 1,3-butadienoic acid methyl ester are fully dispersed in 4800 kg of water as component A;

[0035] (3) 190 kg of acrylic acid, 250 kg of hydroxyethyl acrylate, 250 kg of hydroxypropyl acrylate, 7 kg of methyl acrylate, 8 kg of methacrylate, and 22 kg of L-ascorbic acid are fully dispersed in 720 kg of water as component B;

[0036] (4) At room temperature and under continuous stirring, 25 kg of ferrous sulfate, 10 kg of sodium hypophosphite, and 25 kg of potassium persulfate are sequentially added to the component A obtained in step (2), and after an interval of 10 minutes, 4 kg of mercaptopropionic acid is added thereto, and after an interval of 10 minutes, 1100 kg of the grafted and modified fine sand obtained in step (1) is added thereto, and after an interval of 10 minutes, the component B obtained in step (3) and the alkali solution (the alkali solution is obtained by dissolving 319 kg of sodium hydroxide in 590 kg of water) are sequentially added dropwise thereto, the dropping time of component B is 1.5 h, and the dropping time of the alkali solution is 2 h. After the dropping of the alkali solution is completed, the reaction is continued for 1.5 h;

[0037] (5) Add 6 kg of sulfonated tannin, 50 kg of propylene glycol, and 50 kg of lauryl alcohol to the reaction system obtained in step (4), and then add 2000 kg of water to dilute and disperse the mixture sufficiently to serve as a water retaining agent.

[0038] Example 2

[0039] (1) 20 parts by weight of fine sand (particle size of 400 μm to 600 μm) was ultrasonically dispersed in 1000 parts by weight of ethanol, and 100 parts by weight of vinyl triethoxysilane, 80 parts by weight of ammonia water (NH3 mass concentration of 25%) and 120 parts by weight of water were added thereto, and the mixture was reacted by mechanical stirring at room temperature for 48 hours, and then filtered. The obtained filter cake was fully washed in excess ethanol, centrifuged and dried in vacuum at 60°C to obtain graft-modified fine sand;

[0040] (2) 1500 kg of hexacarbon monomer ethylene glycol vinyl ether polyoxyethylene ether, 1200 kg of acrylamide, 80 kg of polyacrylamide, 20 kg of diacetone acrylamide, and 175 kg of crosslinking agent 1,3-butadienoic acid methyl ester are fully dispersed in 4600 kg of water as component A;

[0041] (3) 180 kg of acrylic acid, 270 kg of hydroxyethyl acrylate, 200 kg of hydroxypropyl acrylate, 5 kg of methyl acrylate, 30 kg of methacrylate, and 23 kg of L-ascorbic acid are fully dispersed in 720 kg of water as component B;

[0042] (4) At room temperature and under continuous stirring, 30 kg of ferrous sulfate, 7.5 kg of antimony glycolate, and 18 kg of ammonium persulfate are added to component A obtained in step (2) in sequence. After an interval of 10 minutes, 4 kg of thioglycolic acid is added thereto. After an interval of 10 minutes, 950 kg of the grafted fine sand obtained in step (1) is added thereto. After an interval of 10 minutes, component B obtained in step (3) and alkali solution (alkali solution is obtained by dissolving 320 kg of potassium hydroxide in 590 kg of water) are added thereto in sequence. The addition time of component B is 1.5 h, and the addition time of alkali solution is 2 h. After the addition of alkali solution is completed, the reaction is continued for 2 h.

[0043] (5) Add 8 kg of sulfonated tannin, 15 kg of propylene glycol, and 60 kg of lauryl alcohol to the reaction system obtained in step (4), and then add 2000 kg of water to dilute and disperse the mixture sufficiently to serve as a water retaining agent.

[0044] Comparative Example 1

[0045] Fine sand was not used as the growth carrier of the hydrophilic network, and the other components and operations were the same as those in Example 1:

[0046] (1) 1400 kg of hexacarbon monomer ethylene glycol vinyl ether polyoxyethylene ether, 1200 kg of acrylamide, 200 kg of polyacrylamide, 50 kg of diacetone acrylamide, and 200 kg of crosslinking agent 1,3-butadienoic acid methyl ester are fully dispersed in 4800 kg of water as component A;

[0047] (2) 190 kg of acrylic acid, 250 kg of hydroxyethyl acrylate, 250 kg of hydroxypropyl acrylate, 7 kg of methyl acrylate, 8 kg of methacrylate, and 22 kg of L-ascorbic acid are fully dispersed in 720 kg of water as component B;

[0048] (3) At room temperature and under continuous stirring, 25 kg of ferrous sulfate, 10 kg of sodium hypophosphite, and 25 kg of potassium persulfate are sequentially added to component A obtained in step (1), and after an interval of 10 minutes, 4 kg of mercaptopropionic acid is added thereto, and after an interval of 10 minutes, component B obtained in step (2) and alkali solution (alkali solution is obtained by dissolving 319 kg of sodium hydroxide in 590 kg of water) are sequentially added dropwise thereto, the addition time of component B is 1.5 h, and the addition time of alkali solution is 2 h. After the addition of alkali solution is completed, the reaction is continued for 1.5 h;

[0049] (4) Add 6 kg of sulfonated tannin, 50 kg of propylene glycol, and 50 kg of lauryl alcohol to the reaction system obtained in step (3), and then add 2000 kg of water to dilute and disperse the mixture sufficiently to serve as a water retaining agent.

[0050] Comparative Example 2

[0051] Fine sand with a particle size of 50 μm to 100 μm is used to replace the fine sand with a particle size of 700 μm to 800 μm in Example 1, and the other components and operations are the same as those in Example 1:

[0052] (1) 20 parts by weight of fine sand (particle size of 50 μm to 100 μm) was ultrasonically dispersed in 1000 parts by weight of ethanol, and 100 parts by weight of vinyl triethoxysilane, 80 parts by weight of ammonia water (NH3 mass concentration of 25%) and 120 parts by weight of water were added thereto, and the mixture was mechanically stirred at room temperature (25° C., the same below) for 48 hours, and then filtered. The obtained filter cake was fully washed in excess ethanol, centrifuged and dried in vacuum at 60° C. to obtain graft-modified fine sand;

[0053] (2) 1400 kg of ethylene glycol vinyl ether polyoxyethylene ether, 1200 kg of acrylamide, 200 kg of polyacrylamide, 50 kg of diacetone acrylamide, and 200 kg of crosslinking agent 1,3-butadienoic acid methyl ester are fully dispersed in 4800 kg of water as component A;

[0054] (3) 190 kg of acrylic acid, 250 kg of hydroxyethyl acrylate, 250 kg of hydroxypropyl acrylate, 7 kg of methyl acrylate, 8 kg of methacrylate, and 22 kg of L-ascorbic acid are fully dispersed in 720 kg of water as component B;

[0055] (4) At room temperature and under continuous stirring, 25 kg of ferrous sulfate, 10 kg of sodium hypophosphite, and 25 kg of potassium persulfate are sequentially added to the component A obtained in step (2), and after an interval of 10 minutes, 4 kg of mercaptopropionic acid is added thereto, and after an interval of 10 minutes, 1100 kg of the grafted and modified fine sand obtained in step (1) is added thereto, and after an interval of 10 minutes, the component B obtained in step (3) and the alkali solution (the alkali solution is obtained by dissolving 319 kg of sodium hydroxide in 590 kg of water) are sequentially added dropwise thereto, the dropping time of component B is 1.5 h, and the dropping time of the alkali solution is 2 h. After the dropping of the alkali solution is completed, the reaction is continued for 1.5 h;

[0056] (5) Add 6 kg of sulfonated tannin, 50 kg of propylene glycol, and 50 kg of lauryl alcohol to the reaction system obtained in step (4), and then add 2000 kg of water to dilute and disperse the mixture sufficiently to serve as a water retaining agent.

[0057] The water-retaining agents prepared in the above-mentioned embodiments and comparative embodiments were used in the same batch of fresh concrete according to the proportions in Table 1, and the effects of the use were tested in accordance with GB / T50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", as shown in Table 2.

[0058] Table 1

[0059] cement 82㎏ Fly ash 9.5㎏ Fine sand 20㎏ gravel 15㎏ Water addition 8㎏ 50% solid polycarboxylic acid collapse-proof solution 1.0㎏ Anti-mud agent PKC832 0.7㎏ FEM concrete anti-segregation agent 0.8㎏ Water Retention Agent 15.0㎏

[0060] Table 2

[0061]

[0062] The blank control in Table 2 refers to the fresh concrete sample without any water retaining agent added, that is, the "water retaining agent" in Table 1 is replaced with water of equal mass, and the other components remain unchanged;

[0063] In Table 2, the detection operation of "slump" is: set a regular trumpet-shaped slump barrel with an upper opening of 100mm, a lower opening of 200mm, and a height of 300mm vertically, and fill the fresh concrete into its inner cavity as evenly as possible in three times. After each filling, use a tamping hammer to knock the barrel wall to achieve compaction. After the last filling, knock and tamp the top of the barrel and smooth it, so that the fresh concrete just fills the inner cavity of the entire barrel. At this time, pull up the barrel, and the fresh concrete will collapse due to its own weight after losing the restriction of the barrel. The difference between the height of the highest point of the concrete after collapse is the difference between the barrel height (300mm) and the height of the highest point of the concrete after collapse, that is, the slump. The larger the slump, the stronger the fluidity of the fresh concrete, and the easier it is to be processed and shaped into various shapes, which is more conducive to construction; on the contrary, the fresh concrete has a large viscosity and is not easy to shape, which is not convenient for construction.

[0064] In Table 2, the blank control example did not use any water retaining agent in the fresh concrete, so the water loss in the concrete was fast, the water loss was serious, the slump was not ideal and decreased significantly, and the workability was not ideal;

[0065] Comparative Example 1 does not load the hydrophilic network onto fine sand, but directly mixes it into the fresh concrete. Compared with the blank control example, it does have a certain water retention effect, but compared with Examples 1 and 2 of this scheme, there is still a gap in the water retention effect. This is because the hydrophilic network in Comparative Example 1 without fine sand as a carrier tends to exist in water. With the deposition of water in the fresh concrete, most of the hydrophilic network is deposited with the water to the middle and lower regions of the fresh concrete, and only a few hydrophilic networks remain in the middle and upper parts, which is equivalent to the water retention agent density in the middle and upper parts of the fresh concrete decreasing at this time; and although the water content in the middle and upper parts of the fresh concrete is also reduced after deposition, the concrete in the middle and upper regions remains moist, which shows that the water is still dispersed in the entire middle and upper regions, and after the hydrophilic network distribution density in this region decreases, it is equivalent to that the part of the water that could originally be contacted by the hydrophilic network loses the intervention of the hydrophilic network, and this part of the water is easily lost, which eventually leads to an increase in the degree of water seepage and water loss in some regions, and the overall fluidity of the concrete is also reduced accordingly.

[0066] In Example 1 and Example 2, the silane coupling agent containing a carbon-carbon double bond is first modified and grafted on the surface of the fine sand, and then the monomer containing a hydrophilic group (such as ethylene glycol vinyl ether polyoxyethylene ether, acrylamide, acrylic acid, hydroxyl acrylate, etc., the carboxyl group, hydroxyl group, amide group, etc. above are all hydrophilic groups) is subjected to addition polymerization reaction with the carbon-carbon double bond on the aforementioned silane coupling agent, so that these hydrophilic monomers are also chemically connected to the surface of the fine sand, wherein the cross-linking agent molecular structure contains two carbon-carbon double bonds, which form a more stable network structure between the polymer chains after participating in the polymerization. The hydrophilic network is based on the inorganic particulate fine sand, which can be stably dispersed in various places inside the concrete to combine and intervene with the water, thereby reducing the water deposition and aggregation of various areas inside the concrete, better retaining the water inside the concrete, and also ensuring the overall processing fluidity of the concrete.

[0067] The fine sand used in Comparative Example 2 has a smaller particle size than that in Example 1, and the water retention effect has also decreased. In this regard, the applicant believes that the fine sand in the present application has an organic hydrophilic network grafted on the surface, so it is an organic-inorganic composite particle, in which the fine sand particles tend to be dispersed and doped in the solid effective components of the concrete, while the hydrophilic network on its surface is more inclined to be combined and dispersed in the water in the concrete, which is equivalent to the two competing with each other in terms of migration trend. After the particle size of the fine sand selected in Comparative Example 2 is reduced, its migration dominance in the concrete decreases, and accordingly, the migration dominance of the hydrophilic network on its surface is relatively enhanced. Therefore, more fine sand migrates with the hydrophilic network and combines with the water in the concrete, and finally deposits. Therefore, this part of the fine sand cannot play the role of "promoting the stable dispersion of water inside the concrete after actively dispersing in the concrete", resulting in a weakened water retention effect.

Claims

1. A method for preparing a composite pulp-raising and water-retaining agent based on six-carbon monomer synthesis, characterized in that: The preparation method is: (1) Grafting modification of fine sand surface by silane coupling agent containing carbon-carbon double bonds Ultrasonic dispersion of the fine sand in an alcohol solvent, and addition of the silane coupling agent containing a carbon-carbon double bond, an alkali agent, and water thereto, stirring for reaction and filtering, fully washing the grafted and modified fine sand, filtering, and drying, wherein the mass ratio of the fine sand, the silane coupling agent containing a carbon-carbon double bond, the alkali agent, the water, and the alcohol solvent is 15-20:5-100:1-50:10-200:300-1500, and the particle size of the fine sand is 700 μm-800 μm; (2) fully mixing one or more of a hexacarbon monomer, acrylamide, and diacetone acrylamide with polyacrylamide and a crosslinking agent to form component A; (3) mixing one or more of acrylic acid, hydroxyethyl acrylate, and hydroxypropyl acrylate, methyl acrylate and / or methacrylate, and a reducing agent to obtain component B; (4) adding the grafted fine sand, catalyst, chain transfer agent and oxidant obtained in step (1) to the component A obtained in step (2) under stirring, and then dripping the component B and alkali solution obtained in step (3) thereto, and continuing the reaction for a period of time after the dripping is completed; (5) adding one or more of sulfonated tannin, sulfonated tannin, glycerol and lauryl alcohol to the reaction system obtained in step (4), and then adding water to dilute and disperse the mixture sufficiently to obtain the water retaining agent.

2. The method for preparing a composite pulp-raising and water-retaining agent based on six-carbon monomer synthesis according to claim 1, characterized in that: In step (1), the alcohol solvent is one or more of methanol, ethanol, n-propanol and isopropanol.

3. The method for preparing a composite pulp-raising and water-retaining agent based on six-carbon monomer synthesis according to claim 1, characterized in that: In step (1), the reaction temperature of the stirring reaction is 20 to 50° C., and the reaction time is 24 to 96 hours.

4. The method for preparing a composite pulp-raising and water-retaining agent based on six-carbon monomer synthesis according to claim 1, characterized in that: In step (2), the cross-linking agent is one or more of 1,3-butadienoic acid methyl ester, 2,3-butadienoic acid ethyl ester, and isoprene.

5. The method for preparing a composite pulp-raising and water-retaining agent based on six-carbon monomer synthesis according to claim 1, characterized in that: In step (2), 200 to 340 parts by weight of one or more of a hexacarbon monomer, acrylamide, and diacetone acrylamide, 5 to 50 parts by weight of polyacrylamide, and 15 to 40 parts by weight of a crosslinking agent are mixed and dispersed in 400 to 600 parts by weight of water.

6. The method for preparing a composite pulp-raising and water-retaining agent based on six-carbon monomer synthesis according to claim 1, characterized in that: In step (3), 50 to 120 parts by weight of one or more of acrylic acid, hydroxyethyl acrylate, and hydroxypropyl acrylate, 1 to 8 parts by weight of methyl acrylate and / or methacrylate, and 1.5 to 2.5 parts by weight of a reducing agent are mixed and dispersed in 60 to 80 parts by weight of water.

7. The method for preparing a composite pulp-raising and water-retaining agent based on six-carbon monomer synthesis according to claim 1, characterized in that: In step (4), the stirring temperature is 20-70° C., the dropwise addition time of component B is 1.5 h, the dropwise addition time of the alkali solution is 1-2 h, and the reaction is continued for 1-2 h after the dropwise addition is completed.

8. A composite pulping and water-retaining agent synthesized based on a six-carbon monomer and prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Concrete conditioning agent and preparation method thereof, concrete admixture and concrete composition

    CN116355141A

  • Organic-inorganic hybrid cross-linked water-retaining agent and preparation method thereof

    CN117089031A